A call for action to establish a research agenda for building a future health workforce in Europe - Ellen Kuhlmann; Ronald Batenburg; Matthias Wismar; Gilles Dussault; Claudia B. Maier; Irene A. Glinos; Natasha Azzopardi-Muscat; Christine Bond; Viola Burau; Tiago Correia; Peter P. Groenewegen; Johan Hansen; et al. (BMC, 2018)
Abstract The importance of a sustainable health workforce is increasingly recognised. However, the building of a future health workforce that is responsive to diverse population needs and demographic and economic change remains insufficiently understood. There is a compelling argument to be made for a comprehensive research agenda to address the questions. With a focus on Europe and taking a health systems approach, we introduce an agenda linked to the 'Health Workforce Research' section of the European Public Health Association. Six major objectives for health workforce policy were identified: (1) to develop frameworks that align health systems/governance and health workforce policy/planning, (2) to explore the effects of changing skill mixes and competencies across sectors and occupational groups, (3) to map how education and health workforce governance can be better integrated, (4) to analyse the impact of health workforce mobility on health systems, (5) to optimise the use of international/EU, national and regional health workforce data and monitoring and (6) to build capacity for policy implementation. This article highlights critical knowledge gaps that currently hamper the opportunities of effectively responding to these challenges and advising policy-makers in different health systems. Closing these knowledge gaps is therefore an important step towards future health workforce governance and policy implementation. There is an urgent need for building health workforce research as an independent, interdisciplinary and multi-professional field. This requires dedicated research funding, new academic education programmes, comparative methodology and knowledge transfer and leadership that can help countries to build a people-centred health workforce.